Government strategies in the water transport sector: A closer look at Philippine ports - Kris A. Francisco; Valerie L. Lim (Philippine Institute for Development Studies (PIDS), 2021)
Transport infrastructure is one of the key elements in achieving a balanced growth within an economy. The water transport sector, in particular, plays a much larger role in an archipelagic country such as the Philippines. The country however, has underinvested in public infrastructure for several years which resulted to low quality of infrastructure and some inefficiencies in the operation of seaports, which are the main infrastructure in the water transport sector. This study analyzed the performance of the Philippine ports through domestic and international lenses by utilizing previous studies and comparative statistics on ASEAN countries. Results show that despite having more international ports, our container and cargo throughput as well as international passenger traffic is lower compared to our ASEAN neighbors. This can be attributed to the perceived low quality of our ports and low level of shipping connectivity. Review of previous studies reveal that issues in the water transport sector are related to quality of infrastructure, inefficiencies in operation and congestion.
Keywords: 330; water transport sector; transport policy; sea ports